Essentials of dental photography - Ahmad, Irfan, BDS (John Wiley & Sons, 2020)
"An accessible, one-stop guide to getting the most out of dental photography in clinical practice Dental photography is an increasingly important part of dental care in general practices, hospitals, and specialist clinics. The uses of dental photographs are numerous, such as monitoring treatment outcomes, educating patients, promoting services, and providing evidence for litigation or regulatory purposes. Essentials of Dental Photography is a user-friendly guide to incorporating dental photographs into daily practice. Containing real-world advice and proven techniques, this book helps clinicians understand and apply the fundamental principles of dental photography. Accessible chapters cover every major aspect of dental photography and answer the most common questions asked by clinicians. Step-by-step instructions show readers how to select the correct photographic and dental equipment, setup equipment for a variety of dental procedures, process images using photo-editing software, and more. The authors, recognised experts in the field, explain the basic concepts of dental photography and how to create high-quality, predictable and repeatable images. Providing an easy-to-follow roadmap to exceptional dental photographs, this practical guide: Covers all the basic concepts, equipment, and techniques of dental photography; Illustrates the photographic setups for both intra- and extra-oral images; Includes easily-referenced chapter summaries and key points of knowledge; Provides recommendations for appropriate types of cameras, lenses, flashes, reflectors, tripods, and software; Discusses photographic archiving, electronic dissemination, printing, publishing, and presenting images"--